Research problems of written monuments in Turkic-kipchak language (ХІІІ-ХV centuries) - Zhubatova, B N; Aubakyrova, К К (Journal of Oriental Studies, 2016)
The article considers the research problems of written monuments (grammar books, glossaries, religion works, etc.) in the Kipchak language in ХІІІ-ХV centuries.